Experimental flowloop study on methane hydrate formation and agglomeration in high water cut emulsion systems - Pham, Trung-Kien; Cameirao, Ana,; Herri, Jean-Michel (HAL CCSD, 2016)
Thème de cette communication: International Conference on Integrated Petroleum Engineering (IPE) International audience hydrate risk also increases. Especially in the offshore systems, operating at low temperature and high pressure, conditions are favourable to the formation of gas hydrate, from the combination of liquid water and gas molecules, under the form of a solid phase. It is a serious issue in the flow assurance; it may cause many troubles, up to plugging.This work brings new understanding on hydrate kinetics of crystallization, nucleation and growth, agglomeration, breakage and deposition under flowing. We focused on high water cut emulsion systems under flowing and we studied the role of commercial anti-agglomerants or low dosage hydrate inhibitors (AA-LDHIs). These additives can disperse hydrate particles to prevent plugging. More specifically, the topic of this study concerns methane hydrate crystallization, agglomeration and hydrate slurry transportation in a flowloop at high water cut systems, with and without AA-LDHI. We have been used up-to-date measurements and calculations among FBRM (Focused Beam Reflectance Measurement), PVM (Particle Video Microscope), pressure, pressure drop, flowrate/density, hydrate conversion and hydrate volume fraction. In this study, we performed the experiments at very high water volume fractions (80-90-100%) in laminar regime (150L/h) with and without anti-agglomerants. The results showed that using gas-lift system (riser), dramatic events were witnessed with a high rate of methane hydrate formation, followed with a quick agglomeration and leading to plugs, even with additive. But we also observed a dramatic foaming event, even at low AA-LDHI concentration of 0.01%.We concluded our work with a discussion of the agglomeration mechanisms, based on a quick hydrate formation and agglomeration rates.